ANALISIS ASUHAN KEPERAWATAN PENUSUKAN ARTERIOVENOUS FISTULA DENGAN INTERVENSI INHALASI AROMATERAPI LAVENDER TERHADAP PENURUNAN PERSEPSI NYERI PADA PASIEN HEMODIALISA DI RUMAH SAKIT BHAYANGKARA TK.I R. SAID SUKANTO - Triyono (2022)
Chronic kidney failure has a high mortality rate compared to tuberculosis and HIV. One of the efforts against end-stage chronic kidney failure is hemodialysis. Vascular access is required for hemodialysis and arteriovenous fistula (AVF) access is the most commonly used in hemodialysis patients. Patients undergoing hemodialysis experience anxiety and pain due to the insertion of hemodialysis needles, an estimated 320 times per year. The pain or perception of pain caused by AVF stabbing can be managed by pharmacological and non-pharmacological therapies or can be combined with both. The purpose of providing this nursing care is to find out whether inhalation of lavender aromatherapy can reduce the pain scale of hemodialysis patients when stabbing arteriovenous fistulas with acute pain problems at Bhayangkara Hospital TK.I R. Said Sukanto. The pain measurement scale instrument used is the Numeric Rating Scale (NRS). The results obtained in this study, reduced pain perception by 2 points from a scale of 4 (moderate pain) to a scale of 2 (mild). Lavender aromatherapy was administered continuously for 5 minutes until the AV fistula was punctured. In this study it can be concluded that inhalation of lavender aromatherapy can reduce pain perception in hemodialysis patients during AV Fistula puncture. Key Word: Acute Pain, Arteriovenous Fistula, Hemodialysis, Lavender Aromatherapy